ECG predictors of T wave oversensing in subcutaneous implantable cardioverter defibrillators. (1st October 2016) - Wilson, D.G.; Leventigiannis, G.; Barr, C.; Morgan, J.M.
Abstract: Background: T wave oversensing (TWOS) is the commonest cause of inappropriate shocks in subcutaneous implantable cardioverter defibrillators (S-ICDs). We hypothesise that predictors of TWOS can be derived from surface ECG parameters. Methods: In a cohort of SICD recipients in two UK centres, all patients who had TWOS (study group) were compared to all those who had not (control group). The pre-implant screen was scanned and the R wave, T wave amplitudes, QRS interval, time to peak T wave, QT interval and R:T ratio was measured using digital callipers. Logistic regression was performed to identify ECG predictors of TWOS. Results: One hundred one patients were studied. Six (5.9%) had TWOS. The mean age of the population was 58.6 ± 18 years and the median follow-up was 19.5 months. By univariate analysis, the predictors of TWOS are QRS duration (140.7 ± 28.7 vs. 105.9 ± 24.6, P = 0.007), time to peak T wave (corrected for heart rate, pTc) (403.9 ± 22.6 vs. 347.8 ± 41.4, P = 0.006), QTc interval (500.4 ± 41.2 vs. 446.8 ± 49.7, P = 0.021), and R:T ratio (3.5 ± 1.1 vs. 9.5 ± 13.2, P = 0.034). By multivariate analysis, time to pTc is the most predictive of TWOS. A time to pTc of 390 ms cut-off point provided a sensitivity 38.5%, a specificity of 98.9%, a positive predictive value for TWOS of 83.3%, and a negative predictive value of 91.6% (AUC = 0.687). Conclusion: In this study, time to pTc is the most powerful ECG predictor of TWOS.